Comparison of bloodstream and non-bloodstream infections caused by carbapenem-resistant Klebsiella pneumoniae in the intensive care unit: a 9-year respective study - Sun, Xiangyuan; Zou, Xiaocui; Zhou, Boting; Yin, Tao; Wang, Ping (Frontiers in Medicine, 2023)
Background: Bloodstream infections (BSIs) caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) have received much attention. However, few studies have identified risk factors for CRKP BSIs in comparison to CRKP non-bloodstream infections (non-BSIs). This study aimed to compare the epidemiology, risk factors, and outcomes of CRKP BSIs and CRKP non-BSIs.We conducted a retrospective study of patients infected with CRKP in the ICU from January 2012 to December 2020. Clinical characteristics and outcomes were compared between CRKP BSIs and CRKP non-BSIs. Predictors associated with 28-day all-cause mortality in CRKP-infected patients were also evaluated.Results: 326 patients infected with CRKP were enrolled, including 96 patients with CRKP BSIs and 230 with CRKP non-BSIs. The rates of CRKP BSIs in CRKP infections were generally raised from 2012 (12.50%) to 2020 (45.76%). Multivariate logistic analysis indicated that the use of carbapenems within the prior 90 days was an independent risk factor for CRKP BSIs (P=0.019). Compared to CRKP non-BSIs, CRKP isolates in the CRKP BSI group were found to be non-susceptible to more tested carbapenems (P=0.001). Moreover, the CRKP BSI group exhibited a higher mortality rate (P=0.036). The non-susceptibility of CRKP isolates to more tested carbapenems (P=0.025), a high SOFA score (P=0.000), and the use of antifungal drugs within the prior 90 days (P=0.018) were significant factors for 28-day all-cause mortality in CRKP-infected patients.The proportion of CRKP BSI increased progressively in CRKP-infected patients over 9 years. The use of carbapenems within the prior 90 days was an independent risk factor for the development of CRKP BSIs. The non-susceptibility of CRKP isolates to more tested carbapenems and a higher mortality rate were found in the CRKP BSI group.